2010
DOI: 10.1002/mnfr.201000027
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of plant sterols reduces plasma and hepatic triglycerides and modulates the expression of lipid regulatory genes and de novo lipogenesis in C57BL/6J mice

Abstract: To investigate emerging clinical data suggesting a triglyceride (TAG)-lowering response to plant sterol (PS) therapy, we characterized changes in TAG metabolism in 16 C57BL/6J mice fed a basal control diet (CON) or the CON diet supplemented with 2% PS for 6 wk. PS consumption reduced (p<0.05) plasma (-28%) and hepatic (-30%) TAG concentrations compared with CON mice. PS consumption increased (p<0.05) hepatic lipogenic gene expression (sterol-regulatory-element-binding protein 1c, 2.4-fold of CON; fatty acid sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 40 publications
5
64
4
2
Order By: Relevance
“…The latter is a surprising observation because previous results from Rideout et al . in C57BL/6J show a decrease in hepatic triglycerides after plant sterol feeding and similar results were found in ApoE Ϫ / Ϫ mice and ApoE3*-Leiden transgenic mice ( 10,25,26 ). The different diet composition used in these studies may explain the variation in hepatic triglyceride levels observed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The latter is a surprising observation because previous results from Rideout et al . in C57BL/6J show a decrease in hepatic triglycerides after plant sterol feeding and similar results were found in ApoE Ϫ / Ϫ mice and ApoE3*-Leiden transgenic mice ( 10,25,26 ). The different diet composition used in these studies may explain the variation in hepatic triglyceride levels observed.…”
Section: Discussionsupporting
confidence: 77%
“…In our study we found a lack of change in plasma cholesterol; however, this result was expected because in earlier studies using C57BL/6J mice, both our own group as well as others observed a lack of effect of plant sterol/stanol consumption on plasma cholesterol concentrations ( 10,24 ). However, we did see a decrease of hepatic cholesterol concentrations, which indicates that plant sterols affect hepatic lipid and lipoprotein metabolism independent of changes in serum cho lesterol concentrations.…”
Section: Discussioncontrasting
confidence: 48%
“…For analysis of hepatic FAs, approximately 0.5 g of pulverized liver was spiked with heptadecanoic acid (C17:0) as an internal standard. Total lipids were isolated from liver tissue with a modified Dole mixture, followed by extraction with heptane, and saponified (36,41). FA extracts were methylated with methanolic boron trifluoride (Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic cholesterol was extracted and analyzed as reported previously (36). Pulverized liver (ϳ500 mg) was spiked with ␣-cholestane as internal standard and saponified, extracted with petroleum diethyl ether, and dried under nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been demonstrated hepatic downregulation of SREBP1 in C57BL/6 mice fed with a mixture of phytosterols in their free forms (Rideout et al 2010). It is well established that the expression of the transcription factor SREBP-1, essential for the transcriptional control of lipogenic genes, is strongly upregulated by the transcription factor LXR.…”
Section: Discussionmentioning
confidence: 99%